Structural Equation Modeling for Analyzing Innovation Adoption in Residential Condominium Projects - Kongkoon Tochaiwat; Vitoon Pawanacharurn; Patcharida Seniwong (Buildings, 2025)
The aim of this study was to analyze innovation acceptance in condominiums using structural equation modeling (SEM) based on latent variables derived from a second-order confirmatory factor analysis (CFA). The authors focused on four groups of latent variables, namely, the characteristics of innovation adopters (CHARACTER), desired innovation categories (CATEGORY), trust in developers (TRUST), and innovation adoption (ADOPTION), collected from an intensive literature review. Data were gathered from 400 residents of high-rise condominiums across twenty-one central districts of Bangkok via purposive sampling. The analysis revealed that only the desired innovation categories had a direct effect on innovation adoption. In contrast, the characteristics of buyers and trust in developers did not have direct effects on innovation adoption but exerted indirect effects through the desired innovation categories. The findings illustrate how SEM can be applied to study the adoption of innovation by real estate buyers. In practical applications, project developers and designers should study which innovations are desired by buyers. This involves considering the buyers’ characteristics and level of trust in the developers. Such an analysis would enable them to design projects that maximize their responsiveness to buyers’ needs and would not impose excessive cost burdens as well as enhancing income opportunities and achieving sustainable competitive advantages.